ESG IMPACT ON FINANCIAL PERFORMANCE AND REPUTATION OF INDUSTRIAL COMPANIES (2020-2025) - Yohan Purnawan; Yeni Trisna Purba; Janulingga Damanik (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) implementation on the financial performance and reputation of industrial companies in Indonesia in the 2020–2025 period, and to identify the role of digital transformation in strengthening the effectiveness of ESG implementation. ESG is positioned as a strategic factor assessed by investors, consumers, regulators, and the public, as the need for sustainable business practices and transparency increases. The study uses a quantitative approach with multiple regression analysis. ESG scores are measured compositely and per dimension (Environmental/E, Social/S, and Governance/G), with financial performance represented by Return on Equity (ROE) and Return on Assets (ROA). Control variables include company size, leverage, and growth, while digital transformation is used as a variable that strengthens ESG implementation through data collection and reporting support. The results show that ESG implementation has a positive and significant effect on financial performance, particularly on increasing ROE and ROA. Furthermore, ESG practices also improve company reputation through transparency and accountability, strengthening brand value, and mitigating reputational risk. Research also confirms that digital transformation supports more efficient and verifiable ESG implementation and reporting processes. A case study of PT Visi Prima Artha, which implemented a solar power plant, reinforces the finding that sustainability initiatives can have a dual impact, improving both financial performance and reputation.